2012
DOI: 10.1111/j.1365-2109.2012.03126.x
|View full text |Cite
|
Sign up to set email alerts
|

An extender solution for the short-term storage ofLitopenaeus vannameisperm to be used in artificial insemination

Abstract: Some shrimp hatcheries use artificial insemination (AI) to improve the male to female ratio in their breeding populations. We describe a sperm extender solution, which allows the short‐term storage of diluted sperm in Litopenaeus vannamei, and its use in an artificial insemination process. We also evaluate its fertilization capacity. An AI experiment was designed using two, one, or half spermatophore segments. We tested four treatments involving three different male:female ratios: Natural mating (1:1), Regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Nevertheless, it is unknown if they keep, or do not keep, their fertilizing potential. A previous study by Morales-Ueno et al (2013) reported successful insemination of females with sperm kept for 4 h, in the same conditions reported in this paper. Therefore, further studies will be important to evaluate the fertilization capability of sperm transported for ~27 h.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, it is unknown if they keep, or do not keep, their fertilizing potential. A previous study by Morales-Ueno et al (2013) reported successful insemination of females with sperm kept for 4 h, in the same conditions reported in this paper. Therefore, further studies will be important to evaluate the fertilization capability of sperm transported for ~27 h.…”
Section: Discussionsupporting
confidence: 79%
“…It is cultured in 33 countries and, for the last five years, its production was 50% of the total world crustacean production (FAO, 2012). Despite the worldwide economic contribution of this species, the use of reproductive technologies to enhance production is scarce (Dong et al, 2004;Nimrat et al, 2006;Ulate & Alfaro-Montoya, 2010;Morales-Ueno et al, 2013). The design of a transportation method for spermatophores would help to disseminate valuable genetic material to enhance production.…”
Section: Introductionmentioning
confidence: 99%
“…Once females were artificially inseminated by using one spermatophore segment (Morales‐Ueno, Montaldo, Martínez, Paniagua‐Chávez & Castillo‐Juárez ), they were individually placed in 200‐L spawning tanks for 6 h, and then placed back into maturation tanks.…”
Section: Methodsmentioning
confidence: 99%
“…The spermatophore, spermatic mass or spermatozoa of crustaceans have been held at room temperature (20–25°C), chilled (2–4°C) or cryopreserved in liquid nitrogen (−196°C) 7,10,196 . For short‐term storage of decapod spermatozoa, most studies reported good sperm viability in the absence of cryoprotectant.…”
Section: Sperm Cryopreservationmentioning
confidence: 99%